Consolidation of Goal-Directed Action Depends on MAPK/ERK Signaling in Rodent Prelimbic Cortex - Hart, Genevra (J Neurosci, 2016)
The prelimbic prefrontal cortex (PL) has consistently been found to be necessary for the acquisition of goal-directed actions in rodents. Nevertheless, the specific cellular processes underlying this learning remain unknown. We assessed changes in learning-related expression of mitogen-activated protein kinase/extracellular signal-related kinase (MAPK/ERK1/2) phosphorylation (pERK) in layers 2–3 and 5–6 of the anterior and posterior PL and in the population of neurons projecting to posterior dorsomedial striatum (pDMS), also implicated in goal-directed learning. Rats were given either a single session of training to press a lever for a pellet reward or yoked reward deliveries without instrumental training and assessed 5 or 60 min after training for pERK expression. Relative to yoked training, instrumental training produced an increase in pERK expression in all regions of the PL both at 5 and 60 min, and this was accompanied by an increase in nuclear pERK expression in the posterior PL in rats given instrumental training. pDMS-projecting neurons showed a transient increase in pERK expression in posterior layer 5–6 projection neurons after 5 min, and a delayed increase in anterior layer 2–3 neurons after 60 min, suggesting that ERK expression in the PL is necessary for the consolidation of goal-directed learning. Consistent with this claim, we found that rats trained on two lever press actions for distinct outcomes and then infused with the MEK inhibitor PD98059 into the PL immediately after training failed to acquire specific action–outcome associations, suggesting that persistent pERK signaling in the PL is necessary for goal-directed learning. SIGNIFICANCE STATEMENT The prelimbic cortex is implicated in goal-directed learning in rodents; however, it is unclear whether it is involved in the consolidation of this learning, and what cellular processes are involved. We used pERK as a marker of activity-related synaptic plasticity to assess learning-induced changes in distinct layers and neuronal populations of the prelimbic prefrontal cortex (PL). Training produced long-lasting upregulation of pERK throughout the PL and specifically within neurons that project to the pDMS, another region critical for goal-directed learning. Next, we demonstrated that pERK signaling in the PL was necessary for the consolidation of goal-directed learning. Together, these results indicate that instrumental training induces ERK signaling in distinct layers and populations in the PL and this signaling underlies the consolidation of goal-directed learning.